Human modeling for bio-inspired robotics : mechanical engineering in assistive technologies - Ueda, Jun (Professor of mechanical engineering); Kurita, Yuichi (Academic Press is an imprint of Elsevier, 2017)
This book presents the most cutting-edge research outcomes in the area of mechanical and control aspects of human functions for macro-scale (human size) applications.